Young children's personal, social and emotional development - Dowling, Marion (London, 2010)
I write this third edition amidst a climate of concern for the world, notably the effects of climate change, the current financial crisis, continuing poverty and ever-increasing violence both in local communities and across continents. The cumulative affect of all of this make it too easy to become negative about the suffering of others and the impact on our own lives. We also cannot help being worried for the future of our youngest children. The Good Childhood report provides powerful evidence of how trends in today's society cause a range of problems for children of all ages (1). At the start of their lives there should be everything to play for but as children grow up today many odds seem stacked against them.
Keywords: Child development; Child psychology